THE INFLUENCE OF ISLAMIC BOARDING SCHOOL DISCIPLINE ON LEARNING BEHAVIOR AND INDEPENDENCE OF STUDENTS OF AL-ITQON ISLAMIC BOARDING SCHOOL - Udhma, Milati; Sugiarti, Rini; Suhariadi , Fendy (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
Islamic boarding schools (Pondok pesantren) as traditional Islamic educational institutions have an important role in shaping the character of students through the application of strict discipline, which is believed to affect learning behavior and independence. This study aims to determine the influence of Islamic boarding school discipline on the learning behavior and independence of students of Al-Itqon Bugen Islamic Boarding School Semarang. The study used an associative quantitative approach with an instrument in the form of a closed questionnaire that included three main variables: discipline, learning behavior, and independence. The research sample consisted of 58 Aliyah grade 2 students who were selected through random sampling techniques. The data were analyzed descriptively, followed by the Kolmogorov-Smirnov normality test, Spearman Rank correlation, and binary logistic regression. The results showed a positive and significant relationship between discipline and learning behavior (r = 0.688; p < 0.001) and independence (r = 0.590; p < 0.001). Logistic regression analysis revealed that students with high discipline had a 12.35 times greater chance of showing high learning behavior and 4.63 times greater to show high independence than students with low discipline. Thus, the discipline applied in the Islamic boarding school environment has proven to be a key factor that supports the development of students' independence and learning behavior significantly.